2008
DOI: 10.1016/j.jmb.2008.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Raman Studies of dsFP483, a Cyan Fluorescent Protein from Discosoma striata

Abstract: To better understand the diverse mechanisms of spectral tuning operational in fluorescent proteins, we have determined the 2.1 Å X-ray structure of dsFP483 from the reef-building coral Discosoma. This protein is a member of the cyan color class of Anthozoa fluorescent proteins, and exhibits broad, double-humped excitation and absorbance bands, with a maximum at 437-400 nm and a shoulder at 453 nm. Although these features support a heterogeneous ground state for the proteinintrinsic chromophore, peak fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
(30 reference statements)
0
20
0
1
Order By: Relevance
“…The reduced extent of charge delocalization upon excitation should result in blue-shifted absorption and emission spectra of amFP486. This explanation may be challenged by recent results from another cyan FP, dsFP483 (78), which has strongly blue-shifted spectra but a (neutral) threonine instead of a histidine residue at the corresponding position.…”
Section: Discussionmentioning
confidence: 91%
“…The reduced extent of charge delocalization upon excitation should result in blue-shifted absorption and emission spectra of amFP486. This explanation may be challenged by recent results from another cyan FP, dsFP483 (78), which has strongly blue-shifted spectra but a (neutral) threonine instead of a histidine residue at the corresponding position.…”
Section: Discussionmentioning
confidence: 91%
“…Understanding the origin of the blueshifted spectral properties of this group has proven rather challenging. The broad absorption/excitation band hints at structural heterogeneity of either the chromophore or the surroundings [86]. By contrast, the narrower emission spectrum signals a unique emitting state.…”
Section: Cyan/teal Groupmentioning
confidence: 99%
“…It is present in Dronpa, a green-emitting FP, and it is missing in cyan dsFP483, in which His at av203 is replaced by a Thr. However, in dsFP483, a different charged residue, a lysine (K70), is in close contact with the chromophore-bridging carbon and points toward the phenolate [86], suggesting that such proximity of a charged residue is indeed necessary.…”
Section: Cyan/teal Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Many other studies have shown that the combined spectroscopic/crystallographic approach is a powerful new tool to investigate these systems. [13] In this work, we use Raman microscopy to investigate the vibrational properties of crystals obtained from wild-type and from SeMet-labelled protein SOUL. We have identified several methionine (Met) and SeMet Raman peaks as useful markers in crystal spectra and managed to unambiguously assign them by comparing the experimental Raman spectra of pure amino acids, recorded in solid-state phase and in aqueous solution with the Raman intensities computed using quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%